Pengaruh Serbuk Gergaji Kayu terhadap Tanah Fat Clay Berdasarkan Indeks Properties Tanah dan Uji UCST - Dona Prillya S; Yulia Morsa Said; Dila Oktarise Dwina (Jurnal Talenta Sipil, 2023)
Soil is the most important thing in development in the field of civil engineering. The bearing capacity of the soil is the ability of the soil to accept and withstand the load transmitted to the soil so that the structure above it does not fail due to poor soil structure. Wood sawdust is a waste of wood industry which has fiber where the fiber can increase the bearing capacity of the soil. This study used sawdust as an additive to the soil with the aim of increasing the carrying capacity of the soil by conducting experiments in the laboratory. This study uses several variants of the percentage of wood sawdust on resistance. The variants are native land, 18%, 20%, 22%, and 24% of 100% of the total percentage of land. From the results of research that has been carried out, it is obtained that the original soil properties index value is 35.89% water content, 2.68 specific gravity, 34.21% PI and soil filter analysis passes filter no.200 95.28%, then based on the uscs soil classification system classified as CH soil: inorganic clay with high plasticity, fat clay, the UCST test on the original soil yielded a value of 2.15 and for soils with a mixture of wood sawdust 2.90 kg/cm2 at a variation of 18%, 3.51 kg/cm2 at a variation of 20 %, 3.27 kg/cm2 at 22% variation, 3.02 kg/cm2 at 24% variation, which shows that there is an increase in UCST value from each variation, but the highest peak occurs at 20% variation.